PATOLOGI BIROKRASI DAN REFORMASI TATA KELOLA PEMERINTAHAN: Kajian Komprehensif terhadap Penyebab, Dampak, dan Strategi Pencegahan dalam Pelayanan Publik di Indonesia - Hidayati, Sri; Andrianti, Andrianti; Netti , Herza; Roza, Silvia; Priyaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article is a comprehensive synthesis study that integrates findings from ten scientific articles on bureaucratic pathology and governance reform in Indonesia. Bureaucratic pathology is defined as deviation or dysfunction within the bureaucratic system that results in a decline in public service quality. This study identifies various forms of bureaucratic pathology including corruption, collusion and nepotism, maladministration, complex procedures, low transparency and accountability, and weak apparatus integrity. The causes of pathology are multidimensional, encompassing structural, cultural, individual, and political-legal dimensions. The impacts are broad: declining public trust, hindered economic development, weakened government legitimacy, and increasing social inequality. In response, this study formulates a layered preventive approach including: (1) structural and procedural reform through digitalization and bureaucratic simplification; (2) strengthening human resource capacity based on the merit system and talent management; (3) organizational culture transformation through the internalization of public administration ethics; (4) consistent application of good governance principles; and (5) strengthening the legal system and public participation. It is concluded that the greatest challenge lies not merely in structural change, but in transforming the deeply rooted mindset and work culture of the apparatus.